Exploring the Mechanism of Clostridium autoethanogenum Protein for Broiler Growth Based on Gut Microbiota and Serum Metabolomics - Chunqiao Shan; Yan Liu; Sisi Liu; Chuang Li; Chaoxin Ma; Hongmin Yu; Juan Li; Guotuo Jiang; Jing Tian (Biology)
Intestinal health is vital for poultry production, and protein plays a key role in intestinal nutrition. The present study used 16S rRNA gene sequencing and serum metabolomics to investigate the effect of CAP on the cecal microflora structure and serum metabolites in 42-day-old broiler chickens. A total of 480 one-day-old Arbor Acres broiler chickens were randomly divided into four treatments with twelve replicates comprising 10 chickens each, evenly divided by sex. The four groups were basal diet group (CAP0), treatment group 1 (CAP2), treatment group 2 (CAP3), and treatment group 3 (CAP4). The broilers in the CAP0 group were fed a basal diet (without CAP), while those in the CAP2, CAP3, and CAP4 groups received diets containing 2%, 3%, and 4% CAP, respectively. Growth performance results showed that dietary CAP supplementation significantly ameliorated the feed conversion rate (FCR) of broilers at 42 days in the CAP3 and CAP4 groups (p < 0.05). Microbial results revealed that CAP did not alter the dominant microorganisms in the cecum at the phylum, family, and genus levels. LEfSe analysis showed significantly higher relative abundances of p_Desulfobacterota, f_Desulfovibrionaceae, and g_Ruminococcus in the CAP3 group compared to the CAP0 and CAP4 groups. Metabolomic analyses indicated that the effect of incorporating CAP into the diet on serum metabolites primarily focused on organic acids and their derivatives, small peptides, amino acid derivatives, and oxidized lipids. The addition of 3% or 4% CAP to the diet can enhance metabolic pathways such as the citrate cycle (TCA cycle) and arginine and proline metabolism. In summary, incorporating CAP into the diet can increase the relative abundance of beneficial bacteria in the cecum and improve the feed conversion efficiency of broilers by enhancing amino acid and energy metabolism.